Chapter 12 Taking drugs to help others - Douglas, Tom (Oxford University Press, 2016)
Some risky medical treatments confer no benefit on the patient who undergoes the intervention though they do benefit third parties. It is commonly thought to be unethical for doctors to provide such treatments even if the patient agrees to undergo them; doing so violates the requirement that medical professionals provide only treatments that are in the best interests of the patient. I present a case for revising this requirement so as to allow individuals to undergo risky medical treatments for the benefit of others.